Integration of a Smart Power Meter for Monitoring Household Energy Consumption in Prepaid Electrical Systems - Permatasari, Indah; Kurnianto, Danny (Jurnal Ilmu Fisika, 2024)
Indonesian households have widely embraced the prepaid electricity payment system. The system relies on electricity credits, with each electrical device consuming credits as a unit of measurement for energy usage. A common issue is the automatic cutoff of electricity supply when the credits are depleted. This research designed a smart power meter using Current Transformer and voltage sensors. The electrical token value is then stored in the Arduino's EEPROM before being transmitted to the NodeMCU. The NodeMCU transfers the data to Antares using the MQTT protocol to forward it to the subscriber, typically an Android device. The data sent to the Android application includes current, voltage, active power, frequency, cos φ, and electrical credits. The measurement of electricity consumption on a kWh meter involves subtracting the value of the input electricity token from the device-measured electricity usage. The device sends a WhatsApp message when the remaining credit exceeds 10 kWh. The prototype of the smart power meter demonstrates practical functionality, with the current sensor accuracy at 99.983% and the voltage sensor accuracy at 99.999%. The largest measurement difference of the electric credit balance between the PLN Meter and the prototype is 0.04 kWh over a test period of 72 hours.